Rodzina w wyobrażeniach pedagogów i w jej rzeczywistych doświadczeniach = The perception of family by educators and in its real experiences - Danilewicz, Wioletta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The research related to the functioning of a family belongs to complex tasks. It attracts the interest of the representatives of numerous scientific disciplines and it intersects the research areas. However, a great deal of research does not reflect the specific experiences of families, their causes, and even consequences.
Keywords: rodzina; pedagogika; badania